Innovative Da'wah Strategies of Border Preachers in Strengthening the Values of Shari'a Islam in the Danau Paris Subdistrict, Aceh Singkil - Tinambunan, Syarbaini; Abdurrahman, Zulkarnain (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
Islamic Sharia in Aceh is implemented as a form of privilege regulated in Law No. 44/1999 on the implementation of the privileges of Aceh Province. Despite the privilege, the implementation of Islamic Sharia in Aceh still faces challenges, especially the low awareness of the community to implement it consistently. This research aims to analyze the strategies applied by da'i in raising public awareness of the implementation of Islamic Sharia in Danau Paris Sub-district, Aceh Singkil District. The focus of this research includes the condition of the implementation of Islamic Sharia in Danau Paris Sub-district, the da'wah strategy used, as well as the identification of challenges faced by da'i. This research uses a descriptive qualitative approach method, where data is obtained through in-depth interviews, participatory observation, and document study. This research reveals that the implementation of Islamic Sharia in Danau Paris Sub-district faces various obstacles, such as low religious understanding in the community, the influence of outside culture and globalization, the economic challenges of the community and the limitations of da'wah facilities. The da'i overcome these challenges through personal and family approaches, social and cultural approaches and collaboration with community leaders and the Islamic Sharia Office. Syariat Islam di Aceh diterapkan sebagai bentuk keistimewaan yang diatur dalam Undang-Undang Nomor 44 Tahun 1999 tentang penyelenggaraan keistimewaan Provinsi Aceh. Meskipun memiliki keistimewaan, penerapan Syariat Islam di Aceh masih menghadapi tantangan, terutama rendahnya kesadaran masyarakat untuk menjalankannya secara konsisten. Penelitian ini bertujuan untuk menganalisis strategi yang diterapkan oleh para da’i Perbatasan dalam Menguatkan Nilai-nilai Syariat Islam di Danau Paris, Kabupaten Aceh singkil. Fokus penelitian ini meliputi kondisi penerapan Syariat Islam di Kecamatan Danau Paris, strategi dakwah yang digunakan, serta identifikasi tantangan yang dihadapi oleh para da’i. Penelitian ini menggunakan metode pendekatan kualitatif deskriptif, yaitu data diperoleh melalui wawancara mendalam, observasi partisipatif, dan studi dokumen. Penelitian ini mengungkapkan bahwa penerapan Syariat Islam di Kecamatan Danau Paris menghadapi berbagai kendala, seperti rendahnya pemahaman agama di masyarakat, pengaruh budaya luar dan globalisasi, tantangan ekonomi masyarakat serta keterbatasan fasilitas dakwah. Para da’i mengatasi tantangan tersebut melalui pendekatan personal dan kekeluargaan,pendekatan sosial dan budaya serta kolaborasi dengan tokoh masyarakat dan Dinas Syariat Islam.